2014
DOI: 10.1021/jp411227r
|View full text |Cite
|
Sign up to set email alerts
|

Coherent and Homogeneous Intramolecular Charge-Transfer Dynamics of 1-tert-Butyl-6-cyano-1,2,3,4-tetrahydroquinoline (NTC6), a Rigid Analogue of DMABN

Abstract: We report the intramolecular charge-transfer (ICT) dynamics of 1-tert-butyl-6-cyano-1,2,3,4-tetrahydroquinoline (NTC6), a planar analogue of 4-(dimethylamino)benzonitrile (DMABN), by using time-resolved fluorescence (TRF) and TRF spectra (TRFS). TRFS allow accurate determination of the ICT dynamics free from the spectral relaxation caused by the solvation and vibronic relaxation. For NTC6 in tetrahydrofuran (THF), the locally excited (LE) state is populated exclusively presumably via a conical intersection fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Experimentally, the gap between the absorption band and the S 1 -LE emission is ~0.7 eV in THF 107 and ~1 eV in vapor phase. 108 The femtosecond time-resolved fluorescence spectrum of DMABN has yet to be measured.…”
Section: Results and Discussion: Ab Initio Multiple Spawning Simmentioning
confidence: 96%
“…Experimentally, the gap between the absorption band and the S 1 -LE emission is ~0.7 eV in THF 107 and ~1 eV in vapor phase. 108 The femtosecond time-resolved fluorescence spectrum of DMABN has yet to be measured.…”
Section: Results and Discussion: Ab Initio Multiple Spawning Simmentioning
confidence: 96%
“…It is clear that right after the formation of the fluorescence signal, at 0.5 ps, an apparent isoemissive point is detected in the TRANES at 594 nm, which is retained during the whole decay process. Instead of a simplistic model based on mere solvation, 19,20 this finding promotes the idea of a two-state deactivation [12][13][14]49 where the first emitting state is completely depopulated within the solvation process (3 ps, cf. concentration profile, Supporting Information, section SI.2, Figure SI The Journal of Physical Chemistry B Article of DASPMI: 49 its TRANES evolution showed two well separated emission bands, whose contributions had previously emerged as a clear enlargement of the stationary fluorescence spectrum in highly polar solvents.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, coupled electron–phonon dynamics can be coherently excited on the polaron PES by impulsive excitation, where the associated reorganization energies (λ) and displacements (Δ) determine the polaron formation pathways 35 , 36 . These coherent dynamics have been detected by using femtosecond time-resolved spectroscopies 37 , 38 . For example, Wang et al 39 recently observed a single coherent wave packet oscillating at ~23 cm −1 in a MAPbI 3 film using femtosecond transient absorption.…”
Section: Introductionmentioning
confidence: 99%